A STUDY OF THE RELATIONSHIP BETWEEN INSTRUCTORS’ PERCEPTION TOWARDS PRESIDENT’S TRANSFORMATIONAL LEADERSHIP AND JOB SATISFACTION IN PU’ER UNIVERSITY YUNNAN - Zuo, Xinrui; Watana Vinitwatanakhun (Scholar: Human Sciences, 2022)
This study was a quantitative study to determine if there is a relationship between the instructor’s perception towards president transformational leadership and job satisfaction in Pu’er University Yunnan Province, China. There were three research objectives in this study: (1) to determine the instructor’s perception of the importance of the president’s transformational leadership, (2) to determine the instructors’ level of Job Satisfaction in Pu’er University Yunnan Province, China, and (3) to determine if there is a relationship between instructor’s perception towards president transformational leadership and job satisfaction in Pu’er University Yunnan Province, China.